2009
DOI: 10.1123/jab.25.3.210
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Age Level on Baseball Hitting Kinematics

Abstract: We propose that learning proper hitting kinematics should be encouraged at a young age during youth baseball because this may help reinforce proper hitting kinematics as a player progresses to higher levels of baseball in their adult years. To enhance our understanding between youth and adult baseball hitting, kinematic and temporal analyses of baseball hitting were evaluated with a high-speed motion analysis system between 12 skilled youth and 12 skilled adult baseball players. There were only a small number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
89
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(111 citation statements)
references
References 15 publications
(40 reference statements)
10
89
5
Order By: Relevance
“…Research findings support the notion that the baseball swing is an example of the kinetic link principle (Escamilla et al, 2009a;Shaffer et al, 1993;Szymanski & DeRenne, 2010;Welch et al, 1995). The kinetic link principle states that larger base segments transfer momentum to smaller adjacent body segments when the action is optimally performed.…”
Section: Hitting In Baseballsupporting
confidence: 68%
See 2 more Smart Citations
“…Research findings support the notion that the baseball swing is an example of the kinetic link principle (Escamilla et al, 2009a;Shaffer et al, 1993;Szymanski & DeRenne, 2010;Welch et al, 1995). The kinetic link principle states that larger base segments transfer momentum to smaller adjacent body segments when the action is optimally performed.…”
Section: Hitting In Baseballsupporting
confidence: 68%
“…The baseball swing has been examined empirically using kinematics and kinetics (Escamilla et al, 2009a;Katsumata, 2007;Welch, Banks, Cook & Draovitch, 1995), electromyography (Shaffer, Jobe, Pink & Perry, 1993) and physics (Cross, 2009). …”
Section: Hitting In Baseballmentioning
confidence: 99%
See 1 more Smart Citation
“…During the baseball batting motion, rotational movement that starts slowly in large segments at the early stage moves towards the point of impact where the bat meets the ball and leads to fast rotation by small segments. The momentum and speed of the bat is greatly affected by such sequential rotational velocity generated by the body segments (Escamilla et al, 2009;Welch et al, 1995). Therefore, the increase in the momentum and the speed of the bat attributed to rotational movement of the body during the batting motion is generated from cooperative contraction of the upper and lower body, and such contraction activities of the muscles also affect the sequential rotational movement of each segment.…”
Section: Discussionmentioning
confidence: 99%
“…Welch et al (1995) reported that in order to increase the bat speed during batting motion, the rotational movement of the pelvis and trunk must be in line with the rotational direction of the bat. Moreover, during the take back motion of the batting motion that prepares player to hit the ball, pelvic and trunk segments must be rotated on a vertical axis in counterclockwise direction, while in the phase when the bat is swung for impact, rotational movement in clockwise direction must be performed (Race, 1961;Escamilla et al, 2009). Rotational movement that starts lead foot to the target direction and quickly rotates the pelvis and trunk segments in counter-clockwise direction to perform the impact movement by moving the bat.…”
Section: Discussionmentioning
confidence: 99%